2022
DOI: 10.1111/dar.13471
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation with injection‐related infections: Validation of diagnostic codes to monitor admission trends at a tertiary care hospital in Melbourne, Australia

Abstract: Introduction. Injection-related infections (IRI) cause morbidity and mortality in people who inject drugs. Hospital administrative datasets can be used to describe hospitalisation trends, but there are no validated algorithms to identify injecting drug use and IRIs. We aimed to validate International Classification of Diseases (ICD) codes to identify admissions with IRIs and use these codes to describe IRIs within our hospital. Methods. We developed a candidate set of ICD codes to identify current injecting dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…ED presentations and hospital separations with an IRI were the outcomes, identified using ICD-10-AM codes in the Victorian Emergency Minimum Dataset and Victorian Admitted Episode Dataset. The ICD-10-AM codes were selected based on a previous study of IRIs in the same setting (Supplementary Table S1) and were identified as ED presentation or hospital separations with any IRI coded (i.e., either as a primary or secondary diagnostic code) [ 13 ]. In Australia, dedicated hospital staff are trained to retrospectively review clinical notes and encode ICD-10-AM data according to strict criteria for the Victorian Admitted Episode Dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ED presentations and hospital separations with an IRI were the outcomes, identified using ICD-10-AM codes in the Victorian Emergency Minimum Dataset and Victorian Admitted Episode Dataset. The ICD-10-AM codes were selected based on a previous study of IRIs in the same setting (Supplementary Table S1) and were identified as ED presentation or hospital separations with any IRI coded (i.e., either as a primary or secondary diagnostic code) [ 13 ]. In Australia, dedicated hospital staff are trained to retrospectively review clinical notes and encode ICD-10-AM data according to strict criteria for the Victorian Admitted Episode Dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Hospitalization data, typically coded using International Classification of Diseases (ICD) codes, can be used to ascertain the incidence of IRIs requiring clinical care that are likely related to injecting drug use [ 12 ]. In Australia, incidence estimates of hospital separations with an IRI are limited to a cohort of people with a history of opioid agonist treatment in New South Wales (43 per 1,000 person-years between 2001 to 2017) and a cohort identified by an algorithm of ICD, Tenth Revision, Australian Modification (ICD-10-AM) codes at a Melbourne health service (192 per 100,000 annual hospital admissions between 2008 and 2018) [ 12 , 13 ]. International incidence estimates of hospital separations with an IRI are also limited to a cohort of people who injected heroin entering community-based substance use treatment in South London (73 per 1,000 person-years between 2006 and 2017) [ 11 ] and people who inject drugs with problematic alcohol use in a Swedish Prison and Probation Service (SSTI, 28.3 per 1,000 person-years and systemic bacterial infection, 9.1 per 1,000 person-years between 2001 and 2014) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colledge‐Frisby et al found that amongst participants accessing OAT in New South Wales between 2001 and 2017, the age‐adjusted incidence rate of hospitalisation for injecting‐related diseases increased from 34.8 to 54.9 per 1000 person years [ 29 ]. A recent Melbourne analysis at a tertiary hospital using International Classification of Diseases codes found that over 12 years between 2008 and 2020, acute infections increased from 138 to 249 per 100,000 admissions [ 34 ]. The burden of admissions was driven by SSTI, which accounted for nearly half of all admissions for people who inject drugs with acute infections (797/1751 = 46%) [ 34 ].…”
Section: Frequency Of Acute Infections In Australiamentioning
confidence: 99%
“…A recent Melbourne analysis at a tertiary hospital using International Classification of Diseases codes found that over 12 years between 2008 and 2020, acute infections increased from 138 to 249 per 100,000 admissions [ 34 ]. The burden of admissions was driven by SSTI, which accounted for nearly half of all admissions for people who inject drugs with acute infections (797/1751 = 46%) [ 34 ]. The majority of SSTI (86.5%, 689/797) were uncomplicated [ 34 ] and thus indicate a potential opportunity for improved early intervention and treatment to prevent hospitalisation.…”
Section: Frequency Of Acute Infections In Australiamentioning
confidence: 99%
See 1 more Smart Citation